Senhores e escravos: tensões do paternalismo em Taubaté (1840-1870) - Chiga, Maurício Vaitsman (2009)
The main objects of this research are certain subtle and ambiguities aspects of the slave holder s paternalism as it existed in Taubaté during the last decades of the 19th century. Our manuscripts sources were wills, registers of purchases and sales of slaves, actions of freedom and criminal proceedings. We selected the years between 1840 s and 1870 s in which to document the growing tensions that threatened the survival of slavery. Tensions between the slave owners rights and the new legal codes that tended to overwrite private intenders of slave owners in behalf the state authority. We also documented simultaneously with this process of a slow dilapidation the owner s power, a rising perception of the possibilities of attaining freedom that expressed itself in the daily lives of slaves and enriched their experience as human beings struggling for opportunities of survival